ANALISIS TINGKAT KEPUASAN JEMAAH HAJI KOTA MEDAN TERHADAP PELAYANAN HAJI TAHUN 2012 - Fitra Jaya (Departemen Ekonomi Pembangunan USU, 2013)
This study aims to analyze the level of satisfaction of pilgrims pilgrimage town with the services field in 2012 and analyze the service attributes that should be corrected by the pilgrim hostel employee field to improve service performance. Data were obtained from 100 people pilgrims making the city terrain with simple random sampling technique. Tests using five indicators of intangible (tangible), reliability (reliability), responsiveness (responsiveness), guarantee or assurance (assurance), and empathy (empathy). The analytical method used is descriptive analysis, Customer satisfaction index (CSI), Importance Analysist (IPA). Validity and reliability with r table value is 0.5%. Analysis of the level of satisfaction of pilgrims pilgrimage town with the services field in 2012 is satisfied that the percentage of 70.7%, which means that the pilgrims are satisfied with the services of the terrain hajj dormitory in 2012. Meanwhile, to improve the satisfaction of the boarding party hajj pilgrims should improve performance on the field attribute the ability of nurses at the time of providing service to the pilgrims, the attention of officials in dealing with pilgrims, and treatment of the pilgrim to pilgrim hostel.Keywords: tangibles, reliability, responsiveness, assurance, emphaty